Streptococcal Superantigens - Babbar, Anshu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book provides ample knowledge and better understanding of Streptococcus pyogenes and their superantigens. Many illustrations make this a highly informative book. This book elucidates briefly Streptococcus pyogenes as a strict human pathogen possessing an array of virulence factors. These help in evading host immune responses such as by the activation of non-specific T-cell subpopulations by producing superantigens. This book mainly focuses on streptococcal superantigens and explains how they are different from conventional antigens. Moreover, it elaborates those diseases in which superantigens are actively involved. Useful aspects of superantigens and different therapeutic interventions to eradicate superantigens induced diseased are also discussed.
Keywords: Life sciences; Microbiology; Life Sciences; Microbiology; Electronic books